Study Protocol: Multimodal Longitudinal Assessment of Infant Brain Organization and Recovery in Perinatal Brain Injury. Issue 2 (18th April 2022) - Saiote, Catarina; Sutter, Ellen; Xenopoulos-Oddsson, Annette; Rao, Raghavendra; Georgieff, Michael; Rudser, Kyle; Peyton, Colleen; Dean, Douglas; McAdams, Ryan M.; Gillick, Bernadette
Abstract : Purpose: Perinatal brain injury is a primary cause of cerebral palsy, a condition resulting in lifelong motor impairment. Infancy is an important period of motor system development, including development of the corticospinal tract (CST), the primary pathway for cortical movement control. The interaction between perinatal stroke recovery, CST organization, and resultant motor outcome in infants is not well understood. Methods: Here, we present a protocol for multimodal longitudinal assessment of brain development and motor function following perinatal brain injury using transcranial magnetic stimulation and magnetic resonance imaging to noninvasively measure CST functional and structural integrity across multiple time points in infants 3 to 24 months of age. We will further assess the association between cortical excitability, integrity, and motor function. Discussion: This protocol will identify bioindicators of motor outcome and neuroplasticity and subsequently inform early detection, diagnosis, and intervention strategies for infants with perinatal stroke, brain bleeds, and related diagnoses.